2010
DOI: 10.1088/1674-1056/19/11/118105
|View full text |Cite
|
Sign up to set email alerts
|

Development of silicon purification by strong radiation catalysis method

Abstract: Ying-Tian(陈应天) a)b)c) † , Ho Tso-Hsiu(何祚庥) c) , Lim Chern-Sing(林晨星) b) , and Lim Boon Han(林文汉) b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…We have already proposed in Refs. [1][2] that a new mechanism, strong radiation catalysis is in the process to speed up the reaction speed. In this paper we shall put forward this hypothesis and discuss in detail based on the experimental results obtained in both the solar and induction furnaces.…”
Section: Basic Experimental Phenomenon and Puzzle Associated With Itmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already proposed in Refs. [1][2] that a new mechanism, strong radiation catalysis is in the process to speed up the reaction speed. In this paper we shall put forward this hypothesis and discuss in detail based on the experimental results obtained in both the solar and induction furnaces.…”
Section: Basic Experimental Phenomenon and Puzzle Associated With Itmentioning
confidence: 99%
“…In fact, one of the motivations to replace the solar furnace by induction furnace in the experiments is to compare the effect of strong black-body radiation with that of concentrated radiations from the Sun. [2] As it has been just mentioned that when the temperature rises from 1900 K to 2200 K, the reaction rate increases 12 times accordingly, if we assume further that the activation energy E ′ R itself is dependent on the black-body radiations, then we shall have…”
Section: A Possible Mechanismmentioning
confidence: 99%
“…In Ref. [1], using these two types of rotations about the axes z and y above as fundamental rotations, they performed the following sequence of four consecutive rotations of a body: rotate the body about the z axis by a small angle −α, then rotate it about y axis by a small angle β, and then about z axis by α, about y by −β. The overall effect of the four steps will not make the body to its initial position which can also be seen from the following result…”
Section: Notations and Backgroundsmentioning
confidence: 99%
“…In Ref. [1], Chen et al showed for a given facet mirror in a mirror array to rotate it to a required orientation in a precision of order three by an 8-step line tilting method. Stimulated by Chen's method, we extend his line tilting method to achieve precision of higher orders by using more steps of line tilting.…”
Section: Introductionmentioning
confidence: 99%
“…Although the sharing of actuators cannot perfectly correct the astigmatic aberration, it does not sacrifice quality of the concentrated sunlight by much, especially the solar concentration ratio of a system. To achieve high solar concentration ratio, Chen et al (2002Chen et al ( , 2005Chen et al ( , 2009Chen et al ( , 2010 had demonstrated that a secondary concentrator of a relatively small size coupled with a primary NIFH was sufficient for a solar furnace system to achieve temperature as high as 3450°C.…”
Section: Introductionmentioning
confidence: 99%